The promise [videorecording (DVD)] - George, Terry; Lebon, Charlotte; Bale, Christian, 1974-; Isaac, Oscar (Universal, 2017)
Empires fall, love survives. When Michael, a brilliant medical student, meets Ana, their shared Armenian heritage sparks an attraction that explodes into a romantic rivalry between Michael and Ana's boyfriend Chris, a famous American photojournalist dedicated to exposing political truth. As the Ottoman Empire crumbles into war torn chaos, their conflicting passions must be deferred while they join forces to get their people to safety and survive themselves.